Smart Hidroponik Berbasis Energi Surya untuk Urban Farming di Kabupaten Gowa - Ilyas Renreng; Luther Sule .; Andi Mangkau .; Zulkilfli Djafar .; Nasruddin Azis .; Muhammad Syahid .; Fauzan .; Asriadi Sakka .; Arfandy . (Faculty of Engineering UNHAS, 2022)
One of the urban farming techniques is hydroponic technique. Hydroponics is a planting technique without using soil media. Hydroponics produces better results than conventional techniques. Planting and growing crops in densely populated areas can be intended for personal consumption or for distribution to others. Especially in the midst of the current COVID-19 condition, where we are faced with the threat of a global food crisis and urban farming is one solution to this. The problem faced by the Bontomarannu community in general is the lack of knowledge about the use of narrow land for hydroponic applications. One of the most efficient and effective types of hydroponics in its use is the NFT (nutrient film technique) hydroponic type. It's just that this type of hydroponics is a type that requires very large operational costs (such as electric pumps) and very complicated maintenance (replacement of nutrients and levels. This is what lies behind the idea of ​​applying science and technology at Bontomarannu in the form of Smart Hydroponics technology as the latest hydroponic technique with an automatic concept based on solar energy. With this, it is hoped that local residents can carry out modern farming activities on a small scale at home with an automatic and energy-free system. The IbM program in the future is expected to continue to be able to provide more education to the surrounding community regarding the development of science and technology, especially implementation of laboratory-based scientific products (LBE) in the Department of Mechanical Engineering, Faculty of Engineering, Hasanuddin University.